2020
DOI: 10.31661/jbpe.v0i0.2003-1084
|View full text |Cite
|
Sign up to set email alerts
|

Brain Functional Mechanisms in Attentional Processing Following Modified Conflict Stroop Task

Abstract: Background: Cognitive control of brain regions can be determined by the tasks involving the cognitive control such as the color word Stroop task. Stroop task define the reduction in function in incongruent condition, which requires more attention and control of competitive responses. Objective: The purpose of this study was to evaluate the activity of brain using the Modified Conflict Stroop Task in Military Personnel. Material and Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…fMRI studies (e.g., Blasi et al, 2006 ) consistently suggested an activation of the DLPFC in relation to tasks (including the Stroop test) that require cognitive control. It is known that the prefrontal region plays a significant role during both congruent and incongruent trials of the Stroop task (Jalalvandi et al, 2020 ). Given its location in the frontal lobes, the DLPFC might be the key neural region that our NIR light stimulation could stimulate, and its involvement may be responsible for the better performance at the eStroop task.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…fMRI studies (e.g., Blasi et al, 2006 ) consistently suggested an activation of the DLPFC in relation to tasks (including the Stroop test) that require cognitive control. It is known that the prefrontal region plays a significant role during both congruent and incongruent trials of the Stroop task (Jalalvandi et al, 2020 ). Given its location in the frontal lobes, the DLPFC might be the key neural region that our NIR light stimulation could stimulate, and its involvement may be responsible for the better performance at the eStroop task.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been shown that PBM may enhance attentional capabilities during a Go/No-Go task (Jahan et al, 2019 ). Recently, the results of a study by Zhu et al ( 2022 ) showed that besides a global cognitive function, PBM supported domain-specific effects improving attention, executive function, and working memory, while no amelioration was found in other subdomains of memory, like naming and visuospatial abilities. However, it is important to note that the three domains associated with PBM exist in a complex relationship.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations